Ce que la nuit raconte au jour - Luc Gwiazdzinski (Ateliers d'Anthropologie)
The article shows the rise of night as a field of interdisciplinary research (night studies). Seeking to go beyond the equation of the night, it highlights the ways in which its exploration has contributed to the day, such as positive disorientation and the learning of a nocturnal way of thinking that makes it possible to manage the contradictions of a hyper-modern society. A sphere for everyone and for no one, the urban night necessitates exchange and cooperation and allows the integration of everyday life issues and sensitive dimensions. This little-explored space-time is conducive to innovation in research methods and tools as well as in public policies. The night also opens the door to some broader prospective areas of investigation relating to notions of temporary citizenship and governance as well as urban time planning. Finally, the article encourages further exploration and measurement: without light, no city at night, but too much light is a killer.